O Camisa 10 em campo: elementos do processo de formação de um futebolista brasileiro - Oliveira, Flávio Ismael da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This research aimed to understand the formative process of soccer player Arthur Antunes Coimbra - Zico. In the condition of a qualitative research, guided by the oral history, and present and contemporary history approaches, we analyzed his experiences and perspectives in search of evidences that enabled us to understand decisive relations to his formation. Different from the current configurations, that ensured the involvement of Zico with footballs and their variations favored a range of significant experiences in the most varied environments. For many years this context prevailed, however, over the years these paths change and become more complex, extensive, exhaustive, expensive, competitive and systematic. The complexity of the process leads us to believe that the initial formative process of the soccer player is under strong contextual influence, including: family, peers, experiences, institutions, professional intervention, teaching and training methodologies, competitive system, awards and many other contexts that comprise formal and informal environments. Considering that soccer today is different from a few decades, and the cultural importance remains so solid in Brazil, we are convinced that training centers must rearrange to respond positively to current and future demands of soccer. Methodologies and tools used in the identification and development of professional soccer players must be reconsidered. By the current context, we believe that the configurations that permeate the formative process leads us to adopt a cautious attitude regarding the possibility emergence of soccer players with the same distinction of Zico and more frequently. Therefore, the formation process can be compromised putting at risk the symbolic prominent position Brazil has on the international sports scene, as one of the leading countries in formation of soccer players

Esta investigação objetivou compreender o processo de formação futebolística de Arthur Antunes Coimbra - Zico. Na condição de uma pesquisa de cunho qualitativo, orientada pelo método de abordagem de história oral e história do tempo presente e contemporânea, analisamos suas experiências e perspectivas em busca de indícios que nos ajudaram a compor relações estabelecidas determinantes para sua formação. Diferente das configurações atuais, as que garantiram o envolvimento de Zico com os futebóis e suas variações favoreceram uma gama de experiências significativas nos mais diversos espaços. Por muitos anos esse contexto prevaleceu, porém, a cada ano que passa, esses caminhos se alteram e se tornam mais complexos, extenso, exaustivo, dispendioso, concorrido e sistemático. A complexidade do processo nos leva a acreditar que a formação inicial do futebolista está sob fortes influências contextuais - família, pares, experiências, instituições, intervenção profissional, metodologias de ensino e treinamento, sistema competitivo e premiação, entre outros que compõem os ambientes informal e formal. Considerando que o futebol de hoje é diferente do futebol de algumas décadas, e que a importância cultural mantém-se tão forte no Brasil, estamos certos de que os centros de formação, para responderem de maneira positiva às exigências atuais e futuras do futebol, precisarão se reorganizar. Será preciso repensar as metodologias e instrumentos utilizados na identificação e desenvolvimento do futuro futebolista profissional. Pelo atual contexto, acreditamos que as configurações que permeiam o processo de formação nos levam a adotar uma postura, mesmo que cautelosa, em relação à possibilidade de surgimento de futebolistas com a mesma expressão de Zico e de maneira mais frequente. Dessa forma, o processo de formação pode estar comprometido colocando em risco a simbólica posição de destaque que...
Keywords: Zico, 1953-; Soccer; Futebol; Historia oral; Formação profissional; Jogadores de futebol; Futebol - Brasil - História